Pengaruh Perceived Value Terhadap Loyalty dan Purchase Intention pada Ragnarok Mobile Game di Jakarta - Diana Chandra didjaja dan Yanuar (Universitas Tarumanagara, 2019)
Huge growth potential has been predicted for in-app purchases and the mobile game market but little is known about what motivates game players to make purchases in mobile game. This study aims to determine the main factors that can influence the purchase intention from players in Ragnarok mobile games. Based on previous research, this study revealed perceived value and loyalty of all players can attract purchase intention. This is a descriptive research by using questionaire which distributed to 120 respondents in Jakarta area. Data was collected by using non probability sampling method. SEM analysis were used for data analysis by using SmartPLS. From this study, it was found that variable perceived value and variable loyalty can influence purchase intention significantly. It was found that loyalty can be a mediator between perceived value and purchase intention.